2020
DOI: 10.1101/2020.09.12.20193086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact and Correlation of Air Quality and Climate Variables with COVID-19 Morbidity and Mortality in Dhaka, Bangladesh

Abstract: The COVID-19 pandemic unexpectedly stopped the steady life and enhanced environmental quality. To apprehend the transmission of COVID-19 and the improvement of air quality, we have studied air quality indicators (PM2.5, PM10, AQI, and NO2), CO2 emission, and climate variables (temperature, relative humidity, rainfall, and wind velocity) in the extremely polluted and densely populated Southeast Asian megacity Dhaka, Bangladesh from March to June 2020. The Kendall and Spearman correlations were chosen to test th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Phase wise lockdown, extended until 30 th May, 2020, led to about two third reduction in ambient levels of SO2 and NO2 as compared to 2019 in same duration (Islam et al, 2021). Studies of Dhaka city have also found a significant correlation between air quality parameters and COVID-19 transmission which confirms that full and partial lockdown helped in flattening the infected cases curve (Pavel et al, 2020;Rahman et al, 2020).…”
Section: Bangladeshmentioning
confidence: 75%
See 1 more Smart Citation
“…Phase wise lockdown, extended until 30 th May, 2020, led to about two third reduction in ambient levels of SO2 and NO2 as compared to 2019 in same duration (Islam et al, 2021). Studies of Dhaka city have also found a significant correlation between air quality parameters and COVID-19 transmission which confirms that full and partial lockdown helped in flattening the infected cases curve (Pavel et al, 2020;Rahman et al, 2020).…”
Section: Bangladeshmentioning
confidence: 75%
“…In order to prevent the spread of virus COVID-19, the Bangladeshi authorities imposed ban on passenger travel via domestic flights, railways and water routes from March 24, 2020 and suspended all public transport from March 26, 2020 (Pavel et al, 2020). However, trucks, and vehicles carrying essential food items, medicine, fuel and other perishable materials were kept out of purview of the lockdown.…”
Section: Bangladeshmentioning
confidence: 99%
“…Research studies have shown that air pollution reduces immune responses in humans, enabling viruses such as the coronavirus to become severe in most cases. The rising trend [22].…”
Section: Sensorsmentioning
confidence: 99%
“…Several studies reported a significant reduction in air pollutants across 91 Indian cities during the month of March 2020, which were leading to in ‘satisfactory’ to ‘good’ category ( Dumka et al, 2020 , Jain & Sharma, 2020 ; Navinya, Patidar & Phuleria, 2020 ; Metya et al, 2020a ; Metya et al, 2020b ; Manisha & Kulshrestha, 2021 ). This drastic improvement in AQI was observed across the Indian sub-continent; AQI was improved in Karachi, Islamabad, and Lahore (Khurshied, 2020; Ali et al, 2020 ), Kathmandu ( Pant et al, 2020 ; Shrestha & Shrestha, 2005 ), and Bangladesh ( Pavel et al, 2020 ; Islam et al, 2021 ).…”
Section: Resultsmentioning
confidence: 90%